2023
DOI: 10.1200/jco.22.01649
|View full text |Cite
|
Sign up to set email alerts
|

Niraparib and Abiraterone Acetate for Metastatic Castration-Resistant Prostate Cancer

Abstract: PURPOSE Metastatic castration-resistant prostate cancer (mCRPC) remains a lethal disease with current standard-of-care therapies. Homologous recombination repair (HRR) gene alterations, including BRCA1/2 alterations, can sensitize cancer cells to poly (ADP-ribose) polymerase inhibition, which may improve outcomes in treatment-naïve mCRPC when combined with androgen receptor signaling inhibition. METHODS MAGNITUDE (ClinicalTrials.gov identifier: NCT03748641 ) is a phase III, randomized, double-blinded study tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(51 citation statements)
references
References 34 publications
0
49
1
1
Order By: Relevance
“…Exploratory analysis in the BRCA1/BRCA2 subgroup showed an HR of 0.24 (95% CI, 0.12 to 0.45) 32 . The MAGNITUDE ( NCT03748641 ) trial also showed improved rPFS with the combination of niraparib plus abiraterone versus placebo plus abiraterone for patients with HRR gene alterations (HR, 0.73; 95% CI, 0.56 to 0.96), with particular benefit in the BRCA1/BRCA2 subgroup (HR, 0.53; 95% CI, 0.36 to 0.79) 33 . Exploratory single-gene analysis of the MAGNITUDE trial, although underpowered, showed potential benefit of combined PARP and androgen receptor inhibition in patients with a Fanconi anemia pathway gene alteration ( PALB2 , BRIP1 and FANCA ) beyond BRCA1/BRCA2 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory analysis in the BRCA1/BRCA2 subgroup showed an HR of 0.24 (95% CI, 0.12 to 0.45) 32 . The MAGNITUDE ( NCT03748641 ) trial also showed improved rPFS with the combination of niraparib plus abiraterone versus placebo plus abiraterone for patients with HRR gene alterations (HR, 0.73; 95% CI, 0.56 to 0.96), with particular benefit in the BRCA1/BRCA2 subgroup (HR, 0.53; 95% CI, 0.36 to 0.79) 33 . Exploratory single-gene analysis of the MAGNITUDE trial, although underpowered, showed potential benefit of combined PARP and androgen receptor inhibition in patients with a Fanconi anemia pathway gene alteration ( PALB2 , BRIP1 and FANCA ) beyond BRCA1/BRCA2 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Novel androgen synthesis and androgen receptor inhibitors, such as abiraterone and enzalutamide, significantly improve the prognosis of CRPC patients, but androgen receptor mutations limit their long-term efficacy [ 3 , 4 ]. Poly (ADP-ribose) polymerase inhibitors, such as olaparib and niraparib, have been approved for use in CRPC treatment by the FDA and EMA, but these agents are limited to CRPC patients bearing mutations in genes involved in homologous recombination repair [ 5 , 35 ]. Hence, there is a great unmet medical need for CRPC treatment due to a lack of effective and nonselective therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…However, in MAGNITUDE, there was a preselection based on HRR-mutation status, while in TALAPRO-2 and PROpel, an unselected (all-comer) population with a substratification based on HRR-mutation status was included. All three studies showed a marked increase in radiographic progression-free survival (rPFS), time to first subsequent therapy or death (TFST), and a trend towards better overall survival (OS) with the use of PARPi in combination with an ARSI, compared to an ARSI alone in the HRR-mutated population, with the greatest benefit in the BRCA-mutated patients (6)(7)(8). MAGNITUDE (Niraparib and Abiraterone Acetate and Prednisone [AAP]) discontinued the non-HRR mutated arm prematurely due to ineffectiveness in the pre-planned futility analysis (6).…”
Section: Introductionmentioning
confidence: 99%
“…All three studies showed a marked increase in radiographic progression-free survival (rPFS), time to first subsequent therapy or death (TFST), and a trend towards better overall survival (OS) with the use of PARPi in combination with an ARSI, compared to an ARSI alone in the HRR-mutated population, with the greatest benefit in the BRCA-mutated patients (6)(7)(8). MAGNITUDE (Niraparib and Abiraterone Acetate and Prednisone [AAP]) discontinued the non-HRR mutated arm prematurely due to ineffectiveness in the pre-planned futility analysis (6). Both TALAPRO-2 (Talazoparib and Enzalutamide) and PROpel (Olaparib and AAP) were conducted in a population of unknown HRR status and showed a benefit for rPFS in the entire population.…”
Section: Introductionmentioning
confidence: 99%